0.1x+0.6y=-2.3

Simple and best practice solution for 0.1x+0.6y=-2.3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.1x+0.6y=-2.3 equation:


Simplifying
0.1x + 0.6y = -2.3

Solving
0.1x + 0.6y = -2.3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.6y' to each side of the equation.
0.1x + 0.6y + -0.6y = -2.3 + -0.6y

Combine like terms: 0.6y + -0.6y = 0.0
0.1x + 0.0 = -2.3 + -0.6y
0.1x = -2.3 + -0.6y

Divide each side by '0.1'.
x = -23 + -6y

Simplifying
x = -23 + -6y

See similar equations:

| 1-7/11=4/11 | | (x^2)-7x+12= | | 9=-8y | | 1-7/11= | | 2tan^2x+3tanx-2=0 | | [5(x-3)]/10 | | 6sec^2x=12 | | 5x-9=3x+27 | | -6x-119=-68 | | x^4-ax^2+1=0 | | [5(×-3)]/10 | | 2x-24=24 | | 9x-(3x+4)=4x-48 | | 196=56-u | | 10-9p=8p | | 6+6(s-3t)= | | 4y^2=12x | | 8p+0(1-p)= | | 8cos^2x-8= | | x=log(8)(11) | | (8t^2-t-4)(8t-1)= | | -7n-26=-21-12n | | (7x-6)(x^2-5x+1)= | | ln(x+2)-3=5 | | 7(3x+2)-5(4x-3)+1=0 | | 180(n-2)=1080 | | (x-3)(2x^2+2x-4)=0 | | x^2+2x-1=18 | | 3t^9(t-t^2+4t^3)= | | 9a+3a+a=9-22 | | 3x-6*0=12 | | 175.00+2.00=3.00x |

Equations solver categories